DISSEMINATED TUBERCULOSIS IN AN IMMUNOCOMPETENT ADULT: AN UNUSUAL CLINICAL MANIFESTATION AND A DIAGNOSTIC CHALLENGE - PRITAM, JEYARAMAN SAI; KANIMOZHI, D.; KANNAN, R. (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Disseminated tuberculosis (TB) constitutes a rare and potentially fatal manifestation of Mycobacterium tuberculosis infection, particularly notable when occurring in immunocompetent individuals. A 52-year-old male with diabetes mellitus presented with a clinical constellation of tachypnea, tachycardia, and chronic lumbar pain. Comprehensive diagnostic imaging revealed pulmonary involvement, destructive changes of the lumbosacral vertebrae (L5-S1), genitourinary tuberculosis, hepatic dysfunction, and bilateral psoas abscesses. Ultrasound-guided aspiration of the abscess, followed by Cartridge-Based Nucleic Acid Amplification Test (CB-NAAT) analysis, confirmed the etiological agent as Mycobacterium tuberculosis. In light of the patient's compromised hepatic function, a modified antitubercular therapy (ATT) regimen was initiated, comprising levofloxacin, amikacin, and ethambutol. The patient exhibited a substantial clinical response, characterized by symptom resolution and normalization of hepatic function during follow-up. This case delineates the diagnostic complexity of disseminated TB in immunocompetent patients, underscoring the criticality of prompt diagnosis and tailored therapeutic strategies. Further investigation is warranted to establish standardized treatment protocols, especially for cases characterized by multi-organ involvement and concomitant hepatic dysfunction.